2020
DOI: 10.1093/jn/nxaa170
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-Rich Beetroot Juice Reduces Blood Pressure in Tanzanian Adults with Elevated Blood Pressure: A Double-Blind Randomized Controlled Feasibility Trial

Abstract: Background In Sub-Saharan Africa, current strategies are struggling to control the burgeoning hypertension epidemic. Dietary interventions such as inorganic nitrate or folic acid supplementation could represent promising strategies for reducing blood pressure (BP) in this setting. Objectives This feasibility study explores the effects of dietary inorganic nitrate supplementation, alone or in combination with folic acid, on BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 28 publications
(33 reference statements)
0
42
0
3
Order By: Relevance
“…The blood was centrifuged for 10 min at 1000× g at 4 °C for plasma collection. The plasma Hcy level was evaluated by a commercially available ELISA kit (Cell Biolabs, San Diego, CA, USA) following the manufacturer's protocol [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The blood was centrifuged for 10 min at 1000× g at 4 °C for plasma collection. The plasma Hcy level was evaluated by a commercially available ELISA kit (Cell Biolabs, San Diego, CA, USA) following the manufacturer's protocol [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Only a handful of trials have explored the medium-to longer-term effects of NO 3 − consumption (4 weeks to 6 months), usually focusing on BP or endothelial function as an outcome. Whilst not a universal finding [67,68], beneficial effects of medium-to longer-term NO 3 − supplementation protocols have been reported in some trials [69][70][71]. For example, Siervo et al [69] found that 2 months supplementation with NO 3 − -rich beetroot juice (~6.5 mmol/d NO 3 − ) decreased 24-h systolic and diastolic BP by − 10.8 and − 5.4 mmHg, respectively, in a Sub-Saharan African setting.…”
Section: Main Textmentioning
confidence: 99%
“…Non-significant decreases in systolic and diastolic lengths occurred following ADR treatment. Dietary nitrate-rich beetroot juice intake exerts positive effects in stable and hypertensive patients by reducing blood pressure [55].…”
Section: Syntheticmentioning
confidence: 99%